Solid waste-based cementitious material and preparation method thereof

Through reasonable ingredients and compound preparation, a kind of solid waste -based gel material is prepared to solve the problem of poor slag and steel slag powder grinding effects and desulfurization gypsum adhesion equipment, and realize the reuse of efficient powder grinding and solid waste.

CN118930087BActive Publication Date: 2025-01-24HEBEI ACAD OF BUILDING RES CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411426089.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

During the grinding process, the uneven distribution of desulfurization gypsum results in poor grinding effect, and the desulfurization gypsum is prone to adhere to the equipment, affecting production.

Method used

Through reasonable ingredients, prepare a solid waste -based gel material, including furnace slag, coal ash, slag, steel residue and desulfurization gypsum, and use a variety of solid waste complication to prepare gel materials to improve the efficiency Adjust the pH value to prevent desulfurization gypsum adhesion.

Benefits of technology

It improves the grinding efficiency of slag and steel slag, avoids desulfurization gypsum from adhering to equipment during the grinding process, reduces grinding energy consumption and drying costs, and achieves efficient reuse of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930087B_ABST
    Figure CN118930087B_ABST
Patent Text Reader

Abstract

The present invention provides a solid waste-based cementitious material and a preparation method thereof, which belongs to the technical field of solid waste recycling. The solid waste-based cementitious material comprises a main component and an external component; the main component, in terms of mass percentage, comprises 10% to 30% of slag, 20% to 40% of fly ash, 30% to 50% of slag and 8% to 17% of steel slag; the external component, in terms of the mass percentage of each part in the total mass of the main component, comprises: desulfurized gypsum and a synergist, and the desulfurized gypsum is 20% to 30% of the slag in the main component according to the mass percentage of each part in the total mass of the main component. oh 矿渣 Selection; the amount of synergist is determined by the pH value after homogenization of all other materials. If the pH value is less than 12.0, the amount is X, where X is the mass ratio of the synergist added to the semi-finished solid waste-based cementitious material when the system pH reaches 12.0-12.8; if the pH value is not less than 12.0, the amount of synergist is 0. The present invention can improve the grinding efficiency of slag and steel slag, improve the strength of solid waste-based cementitious materials, and reduce production costs through reasonable batching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste recycling, and specifically relates to a solid waste-based gelling material and a preparation method thereof. Background Art

[0002] Due to the differences in grindability between slag and steel slag, such as Figure 2 , Figure 3 As shown, when slag and steel slag are mixed with desulfurized gypsum, the proportion of ingredients is crucial to the grinding effect. When the mixed powder is ground to a certain degree, since desulfurized gypsum is easier to grind, the desulfurized gypsum particles can be adsorbed on the surface of slag or steel slag particles. When cracks appear on the surface of slag or steel slag particles due to grinding, the desulfurized gypsum particles will act like wedges, causing the cracks to expand continuously and eventually break apart, thereby improving the grinding effect. If there is too much desulfurized gypsum, it will stick to the surface of slag and steel slag, reducing the grinding effect. If there is too little desulfurized gypsum, the effect on improving the grinding effect is not obvious. Summary of the invention

[0003] The embodiment of the present invention provides a solid waste-based cementitious material and a preparation method thereof, which improves the grinding efficiency of slag and steel slag through reasonable ingredient formulation; at the same time, since the slag and steel slag are finer and have a higher surface area, the desulfurized gypsum is more easily adsorbed on the surface of steel slag and slag, thereby effectively avoiding the problem of desulfurized gypsum easily adhering to equipment during the grinding process and affecting production.

[0004] To achieve the above object, the technical solution adopted by the present invention is: to provide a solid waste-based cementitious material, including: a main component and an external component; the main component, by mass percentage, includes 10% to 30% of slag, 20% to 40% of fly ash, 30% to 50% of slag and 8% to 17% of steel slag;

[0005] The external components are calculated based on the mass percentage of each part in the total mass of the main components, including:

[0006] Desulfurized gypsum, according to the mass percentage of slag in the main components ω 矿渣 , when 30%≤ ω 矿渣 When the content of desulfurized gypsum is less than 37%, the percentage of desulfurized gypsum in the total mass of the main components is (7-0.03 ω 矿渣 ×100)%~(15+0.03) ω 矿渣 ×100)%; when 37%≤ ω 矿渣 When ≤50%, the percentage of desulfurized gypsum in the total mass of the main components is (1.2+0.13 ω 矿渣 ×100)%~(15+0.05) ω 矿渣 ×100)%; and

[0007] The dosage of the synergist is determined by the pH value of the main component and the desulfurized gypsum in the external component after homogenization. If the pH value is less than 12.0, the dosage is X, where X is the mass ratio of the synergist to the semi-finished solid waste-based cementitious material when the system pH reaches 12.0-12.8; if the pH value is not less than 12.0, the dosage of the synergist is 0.

[0008] In combination with the first aspect, in one feasible manner, the slag is circulating fluidized bed slag; the fly ash is fine ash captured from the flue gas after the combustion of coal powder in a coal-fired power plant or a central heating boiler; the slag is water-quenched granulated blast furnace slag produced in the blast furnace steelmaking process; the steel slag is a by-product produced in the converter steelmaking process; and the desulfurization gypsum is a by-product produced in the wet desulfurization process of power plant flue gas.

[0009] In combination with the first aspect, in one achievable manner, the chemical composition and mass fraction of the slag, fly ash, blast furnace slag, steel slag, and desulfurized gypsum are as follows:

[0010] The slag comprises 6% to 11% CaO, 5% to 9% Fe2O3, 45% to 58% SiO2, 20% to 35% A12O3, 1% to 1.8% MgO, 0.6% to 1.4% TiO2, 3% to 7% SO3 and 3% to 9% other components, and the other components are any one or more combinations of Na2O, K2O and P2O5;

[0011] The fly ash comprises 4% to 6% CaO, 4% to 8% Fe2O3, 40% to 56% SiO2, 28% to 37% A12O3, 0.5% to 0.8% MgO, 1.0% to 1.7% TiO2, 0.6% to 1.1% SO3 and 6% to 12% other components, and the other components are any one or more combinations of Na2O, K2O and P2O5;

[0012] The blast furnace slag comprises 26% to 42% CaO, 1% to 7% Fe2O3, 18% to 30% SiO2, 9% to 17% A12O3, 6% to 11% MgO, 0.3% to 1.2% MnO, 1.0% to 7.0% TiO2 and 5% to 9% of other components, and the other components are any one or more combinations of Na2O, K2O, P2O5 and V2O5;

[0013] The steel slag comprises 33% to 43% CaO, 17% to 27% Fe2O3, 13% to 26% SiO2, 2% to 8% A12O3, 3% to 8% MgO, 4% to 6% MnO, 0.5% to 1.0% TiO2 and 5% to 12% other components, and the other components are any one or more combinations of Na2O, K2O, P2O5 and V2O5;

[0014] The desulfurized gypsum includes 40%~50% CaO, 0%~1.5% Fe2O3, 0%~3.5% SiO2, 0.5%~1.5% A12O3, 1%~3.5% MgO, 37%~51% SO3 and 2%~8% of other ingredients, and the other ingredients are any one of Na2O and K2O or a combination of two.

[0015] In a second aspect, an embodiment of the present invention further provides a method for preparing a solid waste-based cementitious material, the method comprising:

[0016] Step 1: Air-dry the desulfurized gypsum until the moisture content is less than 10%, remove the iron from the slag, fix the slag dosage to 30%~50% of the main component, and then mix it with the air-dried desulfurized gypsum in the following proportions:

[0017] The mass percentage of slag in the main components ω 矿渣 , when 30%≤ ω 矿渣 When the content of desulfurized gypsum is less than 37%, the amount of desulfurized gypsum is (0.14 ω 矿渣 ×100)%~(0.17 ω 矿渣 ×100)%; wherein, the amount of desulfurized gypsum is obtained by adding the amount of desulfurized gypsum in the slag gypsum composite powder and the steel slag gypsum composite powder;

[0018] The mass percentage of slag in the main components ω 矿渣 , when 37%≤ ω 矿渣 When the content of desulfurized gypsum is less than 50%, the amount of desulfurized gypsum is (0.13 of the total mass of the main components) ω 矿渣 ×100)%~(0.18 ω 矿渣 ×100)%;

[0019] After the batching is completed, the material is ground once. The material after the first grinding is selected by a high-efficiency powder selector to obtain a specific surface area ≥ 500m 2 / kg and <500m 2 / kg of two materials, of which the specific surface area is less than 500m 2 / kg of materials are returned for primary grinding after iron removal;

[0020] Step 2: The specific surface area in step 1 is ≥ 500m 2 / kg of material is ground twice, and then selected by a high-efficiency powder selector to obtain a specific surface area of ​​650m 2 / kg~670m 2 / kg and <650m 2 / kg of two materials, specific surface area <650m 2 / kg material is removed by plate-type fluidized deironing device and then returned for secondary grinding, with a specific surface area of ​​650m 2 / kg~670m 2 / kg of material as slag gypsum composite powder;

[0021] Step 3: Remove iron from the steel slag particles by hanging iron remover, and dry the desulfurized gypsum and the steel slag after iron removal in hot air furnace to a moisture content of <0.5%, respectively. The amount of steel slag is fixed at 8%~17% of the main component, and then the ingredients are prepared according to the following proportions:

[0022] The mass percentage of slag in the main components ω 矿渣 , when 30%≤ ω 矿渣 When the ratio is less than 37%, the ratio of steel slag to dried desulfurized gypsum is 8-17: (7-0.17 ω 矿渣 ×100)~(15-0.14 ω 矿渣 ×100) proportion of ingredients;

[0023] The mass percentage of slag in the main components ω 矿渣 , when 37%≤ ω 矿渣 When the ratio is ≤50%, the ratio of steel slag to dried desulfurized gypsum is 8~17:1.2~(15-0.13 ω 矿渣 ×100) proportion of ingredients;

[0024] After the ingredients are prepared according to the above mass ratio, they are pre-ground; the pre-ground materials are selected by a V-type powder selector to obtain a specific surface area of ​​≥200m 2 / kg and <200m 2 / kg of two materials, of which the specific surface area is less than 200m 2 / kg of materials are removed by plate-type fluidized deironing device and then returned for pre-grinding;

[0025] Step 4: The specific surface area in step 3 is ≥ 200m 2 / kg of material is ground and then selected by a high-efficiency powder selector to obtain a specific surface area of ​​520m 2 / kg~550m 2 / kg and <520m 2 / kg of two materials, specific surface area <520m 2 / kg of material is removed by plate-type fluidized deironing device and then returned for grinding, with a specific surface area of ​​520m 2 / kg~550m 2 / kg of material as steel slag gypsum composite powder;

[0026] Step 5: The fixed slag dosage is 10%~30% of the main components, and the fly ash dosage is 20%~40% of the main components. After mixing in this proportion, they are put into the ball mill for grinding, and then the powder is selected by the high-efficiency powder selection machine to obtain a specific surface area of ​​550m 2 / kg~590m 2 / kg and <550m 2 / kg of two materials, specific surface area <550m 2 / kg of material is returned to the ball mill for grinding, with a specific surface area of ​​550m 2 / kg~590m 2 / kg of material as slag fly ash composite powder;

[0027] Step 6: transport the slag gypsum composite powder, steel slag gypsum composite powder and slag fly ash composite powder prepared in step 2, step 4 and step 5 according to the mass of the main components to the pneumatic homogenization system for homogenization to obtain a semi-finished solid waste-based cementitious material;

[0028] Step 7: Evenly mix sodium carbonate and calcium hydroxide in a mass ratio of 1:1-2 to obtain a synergist; take m kg of the semi-finished solid waste-based cementitious material and immerse it in 10 m kg of deionized water, stir it for 5 min-10 min, and then let it stand, and test the pH value of the supernatant;

[0029] If the pH value is less than 12.0, slowly add the synergist until the pH value reaches 12.0-12.8, record the amount of synergist added at this time n kg, and obtain the mass ratio of the synergist to the semi-finished solid waste-based cementitious material. X , X =n / m;

[0030] If the pH value is not less than 12.0, there is no need to add a synergist;

[0031] Step 8: The synergist obtained in step 7 and the semi-finished solid waste-based cementitious material are mixed according to their mass ratio, and the mixture is homogenized in the pneumatic homogenization system again to obtain a finished solid waste-based cementitious material.

[0032] In conjunction with the second aspect, in one achievable manner, the sodium carbonate and calcium hydroxide are both analytically pure.

[0033] In combination with the second aspect, in one achievable manner, in step eight, the solid waste-based cementitious material product has a specific surface area of ​​≥550m 2 / kg.

[0034] In combination with the second aspect, in one achievable method, in step 1, the slag is ironed by a hanging iron remover and mixed with the desulfurized gypsum after drying in proportion; the specific surface area is less than 500m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to the vertical mill for further grinding.

[0035] In combination with the second aspect, in one achievable manner, in step one, the primary grinding is performed using a vertical mill; and in step two, the secondary grinding is performed using a ball mill.

[0036] In combination with the second aspect, in one achievable method, in step 3, the desulfurized gypsum after drying and the steel slag after iron removal are mixed according to the mass ratio and then enter the roller press for pre-grinding; in step 4, the specific surface area is ≥200m 2 / kg of material enters the ball mill for grinding.

[0037] Compared with the prior art, the solid waste-based cementitious material provided by the present invention has the following beneficial effects:

[0038] First, the three-pass iron removal of steel slag can improve its grindability and reduce the energy consumption of grinding; the water content of desulfurized gypsum is reduced after drying, and it is mixed with steel slag and dried in a hot air furnace, which can avoid the accumulation and blockage of gypsum with high water content during loading, lifting and transportation, affecting production, and reducing the drying cost; the V-type powder classifier is used after the roller press to break up the caked materials coming out of the roller press, and then separate the qualified fine powder from the broken materials, which is beneficial to the smooth operation of the roller press, improve the system output, and has a drying function; the slag is deironed through three passes, and the vertical mill and ball mill are used for combined grinding to improve the grinding efficiency and reduce energy consumption, while achieving a high degree of controllability of the slag activity and grading.

[0039] Second, the present invention improves the grinding efficiency of slag and steel slag by reasonable batching. At the same time, since slag and steel slag are finer and have a higher surface area, desulfurized gypsum is more easily adsorbed on the surface of steel slag and slag, thereby effectively avoiding the problem of desulfurized gypsum easily adhering to equipment during the grinding process and affecting production.

[0040] Third, solid waste-based cementitious materials are prepared using industrial solid wastes such as metallurgical solid waste and coal-based solid waste. In the alkaline aqueous solution environment system formed by slag, steel slag and desulfurized gypsum, the active components in slag and fly ash are fully hydrated to produce cementitious properties similar to cement. At the same time, fly ash rich in silicon and aluminum components and slag rich in calcium components have complementary components. The present invention utilizes a variety of solid wastes to prepare cementitious materials, which can give full play to the synergistic advantages of multiple solid wastes.

[0041] Fourth, the enhancer is composed of sodium carbonate and calcium hydroxide. Due to the low solubility of calcium hydroxide, it can slowly produce sodium hydroxide, so that the system can maintain an alkaline environment for a long time. On the one hand, it improves the hydration effect, and on the other hand, it can effectively prevent carbonization. At the same time, sodium carbonate and calcium hydroxide will continuously produce sodium hydroxide, which can fill the pores inside the hardening system, increase the density, and enhance durability.

[0042] Fifth, the final grinding process of slag gypsum composite powder, steel slag gypsum composite powder and slag fly ash composite powder all uses ball milling, which can effectively ensure the particle shape; the specific surface area is 650m 2 / kg~670m 2 / kg, 520m 2 / kg~550m 2 / kg and 550m 2 / kg~590m 2 / kg, pneumatic mixing can ensure the excellent gradation of the finished product, ensure that the properties, particle size gradation and particle shape of the finished cementitious material are highly stable and controllable, and achieve the most compact stacking of the finished solid waste-based cementitious material.

[0043] Sixth, the magnetic materials obtained from the suspended iron remover and the plate-type fluidized iron remover in step 1, step 2, step 3, and step 4 can be collected together and sold as magnetic products to create added value. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A process flow chart for preparing a solid waste-based gelling material provided by an embodiment of the present invention;

[0045] Figure 2 A slag grinding characteristic curve diagram provided by an embodiment of the present invention;

[0046] Figure 3 A graph showing the grinding characteristics of steel slag provided in an embodiment of the present invention; DETAILED DESCRIPTION

[0047] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0048] Embodiment 1

[0049] The solid waste-based cementitious material provided by the present invention comprises the following: the slag is circulating fluidized bed slag; the fly ash is fine ash captured from the flue gas after the combustion of coal powder in a coal-fired power plant or a central heating boiler; the slag is water-quenched granulated blast furnace slag produced in the blast furnace steelmaking process; the steel slag is a by-product produced in the converter steelmaking process; and the desulfurized gypsum is a by-product produced in the wet desulfurization process of flue gas in a power plant.

[0050] The main chemical compositions (mass fractions) of the selected fly ash, blast furnace slag, steel slag and desulfurization gypsum are shown in the following table.

[0051] Main chemical composition (mass fraction) of fly ash, blast furnace slag, steel slag and desulfurized gypsum (%)

[0052] chemical composition CaO <![CDATA[Fe2O3]]> <![CDATA[SiO2]]> <![CDATA[A12O3]]> MgO MnO <![CDATA[TiO2]]> <![CDATA[SO3]]> other Slag 6 5 49 30 1.3 — 0.6 5 3.1 Fly ash 5 5 50 31 0.7 — 1.5 0.6 6.2 Blast furnace slag 34 2 27 17 11 0.6 1.5 — 6.9 Steel slag 35 22 14 6.2 7.1 5.5 0.8 — 9.4 Desulfurization gypsum 47 1.3 1.2 0.8 1.6 — — 46 2.1

[0053] The method for preparing a solid waste-based cementitious material provided in Example 1 of the present invention comprises the following steps:

[0054] Step 1: Dry the desulfurized gypsum to 7% water content, remove iron from the slag through a hanging iron remover, fix the slag dosage to 34% of the main component, and then mix it with the dried gypsum in the following proportions:

[0055] The mass percentage of slag in the main components ω 矿渣 is 34%, because 30%≤ ω 矿渣 <37%, add 0.15×0.34×100=5.1% of desulfurized gypsum based on the total mass of the main components.

[0056] After the batching is completed, the materials are put into the vertical mill for grinding. The ground materials are selected by the high-efficiency powder selector to obtain a specific surface area of ​​522m 2 / kg and <500m 2 / kg of two materials, of which the specific surface area is less than 500m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to the vertical mill for grinding.

[0057] Step 2: The specific surface area in step 1 is 522m 2 / kg of material enters the ball mill for secondary grinding, and then is selected by the high-efficiency powder selector to obtain a specific surface area of ​​658m 2 / kg and <650m 2 / kg of two materials, specific surface area <650m 2 / kg is removed by plate-type fluidized deironing device and then returned to ball mill for grinding. The specific surface area is 658m 2 / kg of material is used as slag gypsum composite powder.

[0058] Step 3: Remove iron from the slag particles through a hanging iron remover. The gypsum after drying and the iron-removed slag are dried in a hot air furnace to a moisture content of 0.3%, and the fixed slag dosage is 12% of the main component.

[0059] From step 1, the mass percentage of slag in the main components is ω 矿渣 34%, 30%≤ ω 矿渣 <37%, mix steel slag and dried desulfurized gypsum in a ratio of 10:2;

[0060] After the ingredients are prepared according to the above mass ratio, they are put into the roller press for pre-grinding. The pre-grinded materials are selected by the V-type powder selector to obtain a specific surface area of ​​217m 2 / kg and <200m 2 / kg of two materials, of which the specific surface area is less than 200m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to roller press for grinding.

[0061] Step 4: The specific surface area in step 3 is 217m 2 / kg of material enters the ball mill for grinding, and then is selected by the high-efficiency powder selector to obtain a specific surface area of ​​529m 2 / kg and <520m 2 / kg of two materials, specific surface area <520m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to ball mill for grinding. The specific surface area is 529m 2 / kg of material is used as steel slag gypsum composite powder.

[0062] Step 5: The fixed slag dosage is 28% of the main component, and the fly ash dosage is 26% of the main component. After mixing in this proportion, they are put into the ball mill for grinding, and then the powder is selected by the high-efficiency powder selection machine to obtain a specific surface area of ​​562m 2 / kg and <550m 2 / kg of two materials, specific surface area <550m 2 / kg of material is returned to the ball mill for grinding, with a specific surface area of ​​562m 2 / kg of material is used as slag fly ash composite powder.

[0063] Step six: convey the slag gypsum composite powder, steel slag gypsum composite powder and slag fly ash composite powder prepared according to the mass ingredients of the main components in steps two, four and five to the pneumatic homogenization system for homogenization to obtain a semi-finished solid waste-based cementitious material.

[0064] Step 7: Mix sodium carbonate and calcium hydroxide in a mass ratio of 1:1.2 to obtain a synergist. Take 1.0 kg of the semi-finished solid waste-based cementitious material and immerse it in 10.0 kg of deionized water, stir for 6 minutes and then let it stand. The pH value of the supernatant is tested to be 11.4.

[0065] Since the pH value of the supernatant is less than 12.0, a synergist is added to adjust the pH value to 12.2. At this time, the amount of synergist added is 0.06 kg, and the mass ratio of the synergist to the semi-finished solid waste-based cementitious material is X =0.06.

[0066] Step 8: According to the mass ratio of the synergist obtained in step 7 to the semi-finished solid waste-based cementitious material, the ingredients are mixed and the mixture is homogenized in the pneumatic homogenization system again to obtain a finished solid waste-based cementitious material.

[0067] The surface area of ​​the solid waste-based cementitious material product is 577m 2 / kg.

[0068] Embodiment 2

[0069] Among the solid waste-based cementitious materials, the slag is circulating fluidized bed slag; the fly ash is fine ash captured from the flue gas after the combustion of coal powder in a coal-fired power plant or a central heating boiler; the slag is water-quenched granulated blast furnace slag produced in the blast furnace steelmaking process; the steel slag is a by-product produced in the converter steelmaking process; and the desulfurization gypsum is a by-product produced in the wet desulfurization process of power plant flue gas.

[0070] The main chemical compositions (mass fractions) of the selected fly ash, blast furnace slag, steel slag and desulfurization gypsum are shown in the following table.

[0071] Chemical composition (mass fraction) of fly ash, blast furnace slag, steel slag and desulfurized gypsum (%)

[0072] chemical composition CaO <![CDATA[Fe2O3]]> <![CDATA[SiO2]]> <![CDATA[A12O3]]> MgO MnO <![CDATA[TiO2]]> <![CDATA[SO3]]> other Slag 9 6 46 23 1.6 — 1.2 5.7 7.5 Fly ash 5 7 42 34 0.5 — 1.1 1 9.4 Blast furnace slag 37 5 27 14 9 0.4 1.5 — 6.1 Steel slag 33 21 24 3.8 3.9 6 0.6 — 7.7 Desulfurization gypsum 46 0.2 2 0.7 2.9 — — 44 4.2

[0073] The preparation of the solid waste-based gelling material provided by the present invention comprises the following steps:

[0074] Step 1: Dry the desulfurized gypsum to a moisture content of 3%, remove iron from the slag through a hanging iron remover, fix the slag dosage to 39% of the main component, and then mix it with the dried gypsum in the following proportions:

[0075] The mass percentage of slag in the main components ω 矿渣 is 39%, since 37%≤ ω 矿渣 ≤50%, add 0.16*0.39*100≈6.2% of the total mass of the main components of desulfurized gypsum.

[0076] After the batching is completed, the materials are put into the vertical mill for grinding. The ground materials are selected by the high-efficiency powder selector to obtain a specific surface area of ​​513m 2 / kg and <500m 2 / kg of two materials, of which the specific surface area is less than 500m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to the vertical mill for grinding.

[0077] Step 2: The specific surface area in step 1 is 513m 2 / kg of material enters the ball mill for secondary grinding, and then is selected by the high-efficiency powder selector to obtain a specific surface area of ​​669m 2 / kg and <650m 2 / kg of two materials, specific surface area <650m 2 / kg is removed by plate-type fluidized deironing device and then returned to ball mill for grinding. The specific surface area is 669m 2 / kg of material is used as slag gypsum composite powder.

[0078] Step 3: Remove iron from the slag particles by hanging iron remover. The gypsum after drying and the iron-removed slag are dried in a hot air furnace to a moisture content of 0.4%, and the fixed slag dosage is 15% of the main component.

[0079] From step 1, the mass percentage of slag in the main components is ω 矿渣 39%, 37%≤ ω 矿渣 ≤50%, mix steel slag and dried desulfurized gypsum in a ratio of 12:6.7;

[0080] After the ingredients are prepared according to the above mass ratio, they are put into the roller press for pre-grinding. The pre-grinded materials are selected by the V-type powder selector to obtain a specific surface area of ​​228m 2 / kg and <200m 2 / kg of two materials, of which the specific surface area is less than 200m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to roller press for grinding.

[0081] Step 4: The specific surface area in step 3 is 228m 2 / kg of material enters the ball mill for grinding, and then is selected by the high-efficiency powder selector to obtain a specific surface area of ​​540m 2 / kg and <520m 2 / kg of two materials, specific surface area <520m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to ball mill for grinding. The specific surface area is 540m 2 / kg of material is used as steel slag gypsum composite powder.

[0082] Step 5: The fixed slag dosage is 22% of the main component, and the fly ash dosage is 24% of the main component. After mixing in this proportion, they are put into the ball mill for grinding, and then the powder is selected by the high-efficiency powder selection machine to obtain a specific surface area of ​​566m 2 / kg and <550m 2 / kg of two materials, specific surface area <550m 2 / kg of material is returned to the ball mill for grinding, with a specific surface area of ​​566m 2 / kg of material is used as slag fly ash composite powder.

[0083] Step six: convey the slag gypsum composite powder, steel slag gypsum composite powder and slag fly ash composite powder prepared according to the mass ingredients of the main components in steps two, four and five to the pneumatic homogenization system for homogenization to obtain a semi-finished solid waste-based cementitious material.

[0084] Step 7: Mix sodium carbonate and calcium hydroxide in a mass ratio of 1:1.7 to obtain a synergist. Take 1.0 kg of the semi-finished solid waste-based cementitious material and immerse it in 10.0 kg of deionized water, stir it for 9 minutes and then let it stand. The pH value of the supernatant is tested to be 11.7.

[0085] Since the pH value of the supernatant is less than 12.0, a synergist is added to adjust the pH value to 12.6. At this time, the amount of synergist added is 0.09 kg, and the mass ratio of the synergist to the semi-finished solid waste-based cementitious material is X =0.09.

[0086] Step 8: According to the mass ratio of the synergist obtained in step 7 to the semi-finished solid waste-based cementitious material, the ingredients are mixed and the mixture is homogenized in the pneumatic homogenization system again to obtain a finished solid waste-based cementitious material.

[0087] The surface area of ​​the solid waste-based cementitious material product is 568m 2 / kg.

[0088] Embodiment 3

[0089] The components of the solid waste-based cementitious material are as follows: the slag is circulating fluidized bed slag; the fly ash is fine ash captured from the flue gas after the combustion of coal powder in a coal-fired power plant or a central heating boiler; the slag is water-quenched granulated blast furnace slag produced in the blast furnace steelmaking process; the steel slag is a by-product produced in the converter steelmaking process; and the desulfurization gypsum is a by-product produced in the wet desulfurization process of power plant flue gas.

[0090] The main chemical compositions (mass fractions) of the selected fly ash, blast furnace slag, steel slag and desulfurization gypsum are shown in the following table.

[0091] Chemical composition (mass fraction) of fly ash, blast furnace slag, steel slag and desulfurized gypsum (%)

[0092] chemical composition CaO <![CDATA[Fe2O3]]> <![CDATA[SiO2]]> <![CDATA[A12O3]]> MgO MnO <![CDATA[TiO2]]> <![CDATA[SO3]]> other Slag 7 8 51 20 1.5 — 0.8 3.5 8.2 Fly ash 4 8 47 29 0.6 — 1 0.6 9.8 Blast furnace slag 31 8 25 11 8 0.9 5.2 — 10.9 Steel slag 42 17 16 4.4 6.9 5.7 0.9 — 7.1 Desulfurization gypsum 50 0.8 3.1 1.1 2 — — 38 5.0

[0093] The preparation of the solid waste-based gelling material provided by the present invention comprises the following steps:

[0094] Step 1: Dry the desulfurized gypsum to a moisture content of 6%, remove iron from the slag through a hanging iron remover, fix the slag dosage to 46% of the main component, and then mix it with the dried gypsum in the following proportions:

[0095] The mass percentage of slag in the main components ω 矿渣 is 46%, since 37%≤ ω 矿渣 ≤50%, add 0.15×0.46×100≈6.9% of the total mass of the main components of desulfurized gypsum.

[0096] After the batching is completed, the materials are put into the vertical mill for grinding. The ground materials are selected by the high-efficiency powder selector to obtain a specific surface area of ​​531m 2 / kg and <500m 2 / kg of two materials, of which the specific surface area is less than 500m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to the vertical mill for grinding.

[0097] Step 2: The specific surface area in step 1 is 531m 2 / kg of material enters the ball mill for secondary grinding, and then is selected by the high-efficiency powder selector to obtain a specific surface area of ​​662m 2 / kg and <650m 2 / kg of two materials, specific surface area <650m 2 / kg is removed by plate-type fluidized deironing device and then returned to ball mill for grinding. The specific surface area is 662m 2 / kg of material is used as slag gypsum composite powder.

[0098] Step 3: Remove iron from the slag particles through a hanging iron remover. The gypsum after drying and the iron-removed slag are dried in a hot air furnace to a moisture content of 0.2%, and the fixed slag dosage is 16% of the main component.

[0099] From step 1, the mass percentage of slag in the main components is ω 矿渣 39%, 37%≤ ω 矿渣 ≤50%, mix steel slag and dried desulfurized gypsum in a ratio of 12:7.8;

[0100] After the ingredients are prepared according to the above mass ratio, they are put into the roller press for pre-grinding. The pre-grinded materials are selected by the V-type powder selector to obtain a specific surface area of ​​234m 2 / kg and <200m 2 / kg of two materials, of which the specific surface area is less than 200m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to roller press for grinding.

[0101] Step 4: The specific surface area in step 3 is 234m 2 / kg of material enters the ball mill for grinding, and then is selected by the high-efficiency powder selector to obtain a specific surface area of ​​545m 2 / kg and <520m 2 / kg of two materials, specific surface area <520m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to ball mill for grinding. The specific surface area is 545m 2 / kg of material is used as steel slag gypsum composite powder.

[0102] Step 5: The fixed slag dosage is 15% of the main component, and the fly ash dosage is 23% of the main component. After mixing in this proportion, they are put into the ball mill for grinding, and then the powder is selected by the high-efficiency powder selection machine to obtain a specific surface area of ​​581m 2 / kg and <550m 2 / kg of two materials, specific surface area <550m 2 / kg of material is returned to the ball mill for grinding, with a specific surface area of ​​581m 2 / kg of material is used as slag fly ash composite powder.

[0103] Step six: convey the slag gypsum composite powder, steel slag gypsum composite powder and slag fly ash composite powder prepared according to the mass ingredients of the main components in steps two, four and five to the pneumatic homogenization system for homogenization to obtain a semi-finished solid waste-based cementitious material.

[0104] Step 7: Mix sodium carbonate and calcium hydroxide in a mass ratio of 1:1.9 to obtain a synergist. Take 1.0 kg of the semi-finished solid waste-based cementitious material and immerse it in 10.0 kg of deionized water, stir it for 10 minutes and then let it stand. The pH value of the supernatant is tested to be 12.3.

[0105] Since the pH value of the supernatant is >12.0, no synergist is needed.

[0106] Step 8: According to the mass ratio of the synergist obtained in step 7 to the semi-finished solid waste-based cementitious material, the ingredients are mixed and the mixture is homogenized in the pneumatic homogenization system again to obtain a finished solid waste-based cementitious material.

[0107] The surface area of ​​the solid waste-based cementitious material product is 572m2 / kg.

[0108] The solid waste-based cementitious materials prepared in the above three groups of examples were subjected to general mortar strength, standard consistency water consumption, setting time and stability tests according to T / CECS 689-2020. P·O42.5 cement was used as the comparative example, and the test results are as follows:

[0109] Test results

[0110]

[0111] It can be seen from the test results that the various properties of the solid waste-based cementitious material prepared by the present invention are equal to those of P·O42.5 cement, or even better than those of P·O42.5 cement.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a solid waste-based gelling material, wherein the method comprises: The method comprises: Step 1: Air-dry the desulfurized gypsum until the moisture content is less than 10%, remove the iron from the slag, fix the slag dosage to 30%~50% of the main component, and then mix it with the air-dried desulfurized gypsum in the following proportions: The mass percentage of slag in the main components ω 矿渣 , when 30%≤ ω 矿渣 When the content of desulfurized gypsum is less than 37%, the amount of desulfurized gypsum is (0.14 ω 矿渣 ×100)%~(0.17 ω 矿渣 ×100)%; The mass percentage of slag in the main components ω 矿渣 , when 37%≤ ω 矿渣 When the content of desulfurized gypsum is less than 50%, the amount of desulfurized gypsum is (0.13 of the total mass of the main components) ω 矿渣 ×100)%~(0.18 ω 矿渣 ×100)%; After the batching is completed, the material is ground once. The material after the first grinding is selected by a high-efficiency powder selector to obtain a specific surface area ≥ 500m 2 / kg and <500m 2 / kg of two materials, of which the specific surface area is less than 500m 2 / kg of materials are returned for primary grinding after iron removal; Step 2: The specific surface area in step 1 is ≥ 500m 2 / kg of material is ground twice, and then selected by a high-efficiency powder selector to obtain a specific surface area of ​​650m 2 / kg~670m 2 / kg and <650m 2 / kg of two materials, specific surface area <650m 2 / kg material is removed by plate-type fluidized deironing device and then returned for secondary grinding, with a specific surface area of ​​650m 2 / kg~670m 2 / kg of material as slag gypsum composite powder; Step 3: Remove iron from the steel slag particles by hanging iron remover, and dry the desulfurized gypsum and the steel slag after iron removal in hot air furnace to a moisture content of <0.5%, respectively. The amount of steel slag is fixed at 8%~17% of the main component, and then the ingredients are prepared according to the following proportions: The mass percentage of slag in the main components ω 矿渣 , when 30%≤ ω 矿渣 When the ratio is less than 37%, the ratio of steel slag to dried desulfurized gypsum is 8-17: (7-0.17 ω 矿渣 ×100)~(15-0.14 ω 矿渣 ×100) proportion of ingredients; The mass percentage of slag in the main components ω 矿渣 , when 37%≤ ω 矿渣 When the ratio is ≤50%, the ratio of steel slag to dried desulfurized gypsum is 8~17:1.2~(15-0.13 ω 矿渣 ×100) proportion of ingredients; After the ingredients are prepared according to the above mass ratio, they are pre-ground; the pre-ground materials are selected by a V-type powder selector to obtain a specific surface area of ​​≥200m 2 / kg and <200m 2 / kg of two materials, of which the specific surface area is less than 200m 2 / kg of materials are removed by plate-type fluidized deironing device and then returned for pre-grinding; Step 4: The specific surface area in step 3 is ≥ 200m 2 / kg of material is ground and then selected by a high-efficiency powder selector to obtain a specific surface area of ​​520m 2 / kg~550m 2 / kg and <520m 2 / kg of two materials, specific surface area <520m 2 / kg of material is removed by plate-type fluidized deironing device and then returned for grinding, with a specific surface area of ​​520m 2 / kg~550m 2 / kg of material as steel slag gypsum composite powder; Step 5: The fixed slag dosage is 10%~30% of the main components, and the fly ash dosage is 20%~40% of the main components. After mixing in this proportion, they are put into the ball mill for grinding, and then the powder is selected by the high-efficiency powder selection machine to obtain a specific surface area of ​​550m 2 / kg~590m 2 / kg and <550m 2 / kg of two materials, specific surface area <550m 2 / kg of material is returned to the ball mill for grinding, with a specific surface area of ​​550m 2 / kg~590m 2 / kg of material as slag fly ash composite powder; Step 6: transport the slag gypsum composite powder, steel slag gypsum composite powder and slag fly ash composite powder prepared in step 2, step 4 and step 5 according to the mass of the main components to the pneumatic homogenization system for homogenization to obtain a semi-finished solid waste-based cementitious material; Step 7: Evenly mix sodium carbonate and calcium hydroxide in a mass ratio of 1:1-2 to obtain a synergist; take m kg of the semi-finished solid waste-based cementitious material and immerse it in 10 m kg of deionized water, stir it for 5 min-10 min, and then let it stand, and test the pH value of the supernatant; the synergist is composed of sodium carbonate and calcium hydroxide. Since calcium hydroxide has low solubility, sodium hydroxide can be slowly produced, so that the system can maintain an alkaline environment for a long time, which can improve the hydration effect on the one hand and effectively prevent carbonization on the other hand; at the same time, sodium carbonate and calcium hydroxide will continuously produce sodium hydroxide, which can fill the pores inside the hardening system, improve the density, and enhance the durability; If the pH value is less than 12.0, slowly add the synergist until the pH value reaches 12.0-12.8, record the amount of synergist added at this time n kg, and obtain the mass ratio of the synergist to the semi-finished solid waste-based cementitious material. X , X =n / m; If the pH value is not less than 12.0, there is no need to add a synergist; Step 8: mixing the synergist obtained in step 7 with the semi-finished solid waste-based gelling material in a mass ratio, and then entering the pneumatic homogenization system for homogenization again to obtain a finished solid waste-based gelling material; The solid waste-based cementitious material comprises: a main component and an external component; the main component comprises, by mass percentage, 10% to 30% of slag, 20% to 40% of fly ash, 30% to 50% of slag and 8% to 17% of steel slag; The external components are calculated based on the mass percentage of each part in the total mass of the main components, including: Desulfurized gypsum, according to the mass percentage of slag in the main components ω 矿渣 , when 30%≤ ω 矿渣 When the content of desulfurized gypsum is less than 37%, the percentage of desulfurized gypsum in the total mass of the main components is (7-0.03 ω 矿渣 ×100)%~(15+0.03) ω 矿渣 ×100)%; when 37%≤ ω 矿渣 When ≤50%, the percentage of desulfurized gypsum in the total mass of the main components is (1.2+0.13 ω 矿渣 ×100)%~(15+0.05) ω 矿渣 ×100)%; and The dosage of the synergist is determined by the pH value of the desulfurized gypsum in the main component and the external component after homogenization. If the pH value is less than 12.0, the dosage is X , X In order to make the system pH reach 12.0~12.8, the mass ratio of the synergist to the semi-finished solid waste-based cementitious material is added; if the pH value is not less than 12.0, the amount of synergist is 0.

2. The method for preparing solid waste-based gelling material according to claim 1, characterized in that: The sodium carbonate and calcium hydroxide are both analytically pure.

3. The method for preparing solid waste-based cementitious materials according to claim 1, characterized in that: In step 8, the solid waste-based cementitious material product has a specific surface area of ​​≥550m 2 / kg.

4. The method for preparing solid waste-based gelling material according to claim 1, characterized in that: In step 1, the slag is ironed by a hanging iron remover and mixed with the desulfurized gypsum after drying in proportion; the specific surface area is less than 500m 2 / kg of material is removed by plate-type fluidized deironing device and then returned to the vertical mill for further grinding.

5. The method for preparing solid waste-based cementitious materials according to claim 1, characterized in that: In step 1, a vertical mill is used for primary grinding; and in step 2, a ball mill is used for secondary grinding.

6. The method for preparing solid waste-based cementitious materials according to claim 1, characterized in that: In step 3, the desulfurized gypsum after drying and the steel slag after iron removal are mixed according to the mass ratio and then enter the roller press for pre-grinding; in step 4, the specific surface area ≥ 200m 2 / kg of material enters the ball mill for grinding.

7. The method for preparing solid waste-based gelling material according to claim 1, characterized in that: The slag is circulating fluidized bed slag; the fly ash is fine ash captured from the flue gas after the combustion of coal powder in a coal-fired power plant or a central heating boiler; the slag is water-quenched granulated blast furnace slag produced in the blast furnace steelmaking process; the steel slag is a by-product produced in the converter steelmaking process; and the desulfurized gypsum is a by-product produced in the wet desulfurization process of power plant flue gas.

8. The method for preparing solid waste-based gelling material according to claim 1, characterized in that: The chemical composition and mass fraction of the slag, fly ash, blast furnace slag, steel slag and desulfurized gypsum are as follows: The slag comprises 6% to 11% CaO, 5% to 9% Fe2O3, 45% to 58% SiO2, 20% to 35% A12O3, 1% to 1.8% MgO, 0.6% to 1.4% TiO2, 3% to 7% SO3 and 3% to 9% other components, and the other components are any one or more combinations of Na2O, K2O and P2O5; The fly ash comprises 4% to 6% CaO, 4% to 8% Fe2O3, 40% to 56% SiO2, 28% to 37% A12O3, 0.5% to 0.8% MgO, 1.0% to 1.7% TiO2, 0.6% to 1.1% SO3 and 6% to 12% other components, and the other components are any one or more combinations of Na2O, K2O and P2O5; The blast furnace slag comprises 26% to 42% CaO, 1% to 7% Fe2O3, 18% to 30% SiO2, 9% to 17% A12O3, 6% to 11% MgO, 0.3% to 1.2% MnO, 1.0% to 7.0% TiO2 and 5% to 9% of other components, and the other components are any one or more combinations of Na2O, K2O, P2O5 and V2O5; The steel slag comprises 33% to 43% CaO, 17% to 27% Fe2O3, 13% to 26% SiO2, 2% to 8% A12O3, 3% to 8% MgO, 4% to 6% MnO, 0.5% to 1.0% TiO2 and 5% to 12% other components, and the other components are any one or more combinations of Na2O, K2O, P2O5 and V2O5; The desulfurized gypsum includes 40%~50% CaO, 0%~1.5% Fe2O3, 0%~3.5% SiO2, 0.5%~1.5% A12O3, 1%~3.5% MgO, 37%~51% SO3 and 2%~8% of other ingredients, and the other ingredients are any one of Na2O and K2O or a combination of two.

Citation Information

Patent Citations

  • High-performance concrete admixture and production method thereof

    CN113213802A

  • Batching calculation method of all-solid waste cementing material

    CN117253569A